Dental Materials: Latest Advances and Prospects - Checchi, Vittorio (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Almost all fields of dentistry are closely related to newly developed materials, and all clinical improvements often follow, or, in any case, go hand in hand with the creation and the development of innovative and higher performing materials, instruments, and equipment. Thanks to contemporary applications of dental materials, the effectiveness of clinical dentistry has made remarkable advances. In recent years, thanks to digital technology and the frenetic development of the dental industry, new materials have been developed and proposed in many fields of dentistry: prosthesis, restorative dentistry, endodontics, implantology, and orthodontics. Unfortunately, as often happens, this productive challenge is not always accompanied by valid scientific research, and consequently the clinician finds new materials at their disposal that are not necessarily better than the old. Further studies are needed to gain relevant evidence for all recently introduced dental materials. This reprint includes research articles, clinical studies, review articles, and case reports focused on the latest advances and prospects of dental materials concerning all fields of dentistry.